THORACIC OUTLET SYNDROME COMPLICATED BY DOUBLE SUBCLAVIAN ARTERY ANEURYSMS — AN HYBRID APPROACH - Castro-Ferreira, Ricardo (2017)
Introduction: Subclavian artery aneurysm (SAA) can be an extremely rare complication of thoracic outlet syndrome (TOS). The arterial dilation usually occurs distal to the stenosis site causing TOS. We describe a rare case of a patient with neurological TOS with two voluminous SAA proximal and distal to interscalene triangle. Case report: A 55 years-old female patient, with no prior medical conditions, was referred to vascular surgery clinic with symptoms of neurological TOS. The radial pulses were absent in the affected limb but the patient had no arterial complains. In the work-up angio-CT two consecutive SAA (31 and 42mm) divided by anterior scalenus muscle were diagnosed. The aneurysms were excluded by covered stent angioplasty after circle of Willis flow assessment by transcranial Doppler. Subsequently the patient was submitted to anterior scalenectomy in operating theatre. The symptoms completely reversed and the patient was discharged two days after surgery. Follow-up angio-CT confirmed SAA exclusion. Patient remains asymptomatic 6 months after the treatment. Discussion: The term thoracic outlet syndrome was originally used in 1956 by RM Peet to designate compression of the neurovascular bundle at the thoracic outlet3. Since its original description, a multitude of clinical entities was associated with TOS. SAA is a rare but potential dangerous complication of TOS. Whereas historically SAA have been managed by open surgery, the novel endovascular methods offer an elegant and safer approach to this condition. Although first rib resection is emerging as the regular method of thoracic outlet decompression, this particular case imaging was highly suggestive of scalenus muscle compression. This case exemplifies how endovascular and open approaches can elegantly work together with remarkable results. To the best of our knowledge, this is the first description of a double subclavian artery aneurysm in the context of TOS.